(3OhQ GdMjGRI aj GdQgf GdMjGRj (B:s (3OQGSI ehGRfI Hjf GdJTQjYGJ GdhVYjI h GdJTQjYI GdGSdGejI (B/s - (3QLjH, HjGf jhSas ((3YeGf(B: s (3OGQ GdKbGaI(B, s, 2010)
(3eGgjI GdRgf h eGgjI GdMjGRI (B1) (3OhQ GdMjGRI aj fThA GdQgf h faGPg (B: (3ehba GdJTQjYGJ GdhVYjI h Gdabg GdGSdGej ef GdMjGRI , GfJbGd GdMjGRI Cj GdGbHGV , YfGUQ SjQGf GdMjGRI h CKQ faGP GdQgf aj ehGLgI GdZjQ (B2) (3CMcGe GdQgf GdMjGRj GdeQJHWI HGdMjGRI (B: (3GdJRGeGJ GdOGFf GdeQJgf h Mbhbg , Mbhb h GdJRGeGJ GdQGgf GdeQJHWI HGdMjGRIs
(3eQGLY U(B.517s
Keywords: (3GdQgfs; (3GdQgf GdMjGRjs; (3GdQgf GdYbGQj GdMjGRjs